Interpretation of Inheritance in Qur'an Surah An-Nisā` verse 11 - Ibnudin (Penerbit Hellow Pustaka, 2024)
As we know, the distribution of inherited assets in society often raises problems and results in divisions within the family. Unfair distribution and not knowing how to divide inheritance are the causes. Whether we admit it or not, the distribution of inheritance within the family is something that is very sensitive. However, the problem is that today's science councils pay little attention to learning about the science of faraidh. So it is true what the Prophet said in the hadith above that inherited knowledge is knowledge that will be forgotten and now we are starting to experience it together. With the gradual disappearance of the science of faraidh, many people are realizing that conflicts can often arise in society.